Prevalence and pathology of ectoparasites of Mediterranean fish, reared under three different environmental and aquaculture conditions in Greece - VAGIANOU (ΒΑΓΙΑΝΟΥ ΣΤ), St.; ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), F.; RAGIAS (Β ΡΑΓΙΑΣ), V.; di CAVE, D.; LEONTIDIS (Λ. ΛΕΟΝΤΙΔΗΣ), L.; GOLOMAZOU (Ε. ΓΚΟΛΟΜΑΖΟΥ), E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Sea bream Spams aurata L. and sea bass Dicentrarchus labraxL. were sampled from three different locations in Greece (2 cage fish farms located in different geographic areas and a lagoon), in order to investigate the prevalence of Metazoa parasites, the intensity and the factors associated with the prevalence. In farm 1 (Eastern Greece) the prevalence of the ectoparasites was: 61.5% and 76.9% for Monogenea, 0% for Isopoda and 0% and 23% for Copepoda in sea bream and sea bass, respectively. In farm 2 the prevalence was: 13.3% and 26.3% for Monogenea, 13.7% and 20% for Isopoda and 0% and 13.6% for Copepoda in sea bream and sea bass, respectively. Lesions in the gills of Sparidae were due to monogeneans, but lesions in the skin and eyes were due to Ceratothoa oestroides larval stages causing severe pathology. Furnestinia. echeneis and Diplectanum aequans were host specific for sea bream and bass, respectively and showed persistence in all aquaculture systems. The Greek lagoon had the largest variety of parasites among the ecosystems studied, however, this variety did not significantly affect the health of infected fish. Lernanthropus kroyeri was host specific and was detected only in sea bass in both cage farms investigated.